Outcome in acute ischemic stroke patients with large-vessel occlusion and initial mild deficits - Kazmi, Jacob S.; O'Hara, Joseph; Gandomi, Amir; Wang, Jason J.; Sanmartin, Maria X.; Yang, Bo; Sanelli, Pina C.; Katz, Jeffrey M. (Frontiers in Stroke, 2024)
Background The management of patients with initially mild acute ischemic stroke (AIS), defined by the National Institutes of Health Stroke Scale (NIHSS) scores 0–5, remains ambiguous despite advances in stroke treatment. The early identification of patients likely to deteriorate is critical in preventing lasting disability. Aims We investigated the frequency and early predictors of poor functional outcomes in AIS patients with large-vessel occlusion (LVO) and initial mild deficits. Methods We performed a retrospective observational study of consecutive AIS patients admitted to a single comprehensive stroke center between 2018 and 2021. The inclusion criteria were a diagnosis of AIS, an arrival NIHSS score of 0–5, imaging-confirmed LVO, and arrival within 24 h of the last-known-well time. The primary outcome was the change in the discharge-modified Rankin Score (ΔmRS) from baseline, categorized as 0–1 (stable outcome) or >1 (poor outcome). Early neurological deterioration was defined as a mean NIHSS score increase of >1 in the first 24-h period. Univariate and multivariable regression analyses were performed. The mean daily NIHSS scores were compared between groups using an analysis of variance (ANOVA). Results Of 4,410 stroke admissions, 120 patients met the study inclusion criteria, with 71 (59.2%) patients having a ΔmRS of 0–1 and 49 (40.8%) patients having a ΔmRS of > 1. The mean arrival NIHSS score was similar between groups. However, the mean first-24-h NIHSS score was significantly higher in the poor outcome group vs. the stable outcome group (2.13 vs. 0.95, p < 0.001). A demographic-adjusted multivariable logistic regression revealed that a higher mean first-24-h NIHSS score was the sole early predictor of poor outcome (odds ratio [OR] of 1.65 and a 95% confidence interval [CI] of [1.18, 2.48]). The only association with early neurological deterioration was vertebral artery occlusion, with an OR of 0.35 and a 95% CI of [0.14, 0.81]. The trending mean daily NIHSS scores revealed that patients with poor outcomes deteriorate within 24 h, a significant difference from the stable group (p < 0.001). Conclusion Poor outcomes occurred in a significant proportion of LVO patients with initial mild deficits. The only association was early neurological deterioration. To prevent poor outcomes, rapid identification of any clinical deterioration should prompt consideration of thrombectomy.